Reduction in ocean heat loss in Antarctic dense water formation regions from 1980 to 2024 using ERA5 - Machín, Francisco; Olivé Abelló, Anna (Frontiers in Marine Science, 2025)
This study uses ERA5 output to investigate long-term trends and interannual variability in surface heat fluxes across the main Antarctic dense water formation regions in Antarctica—Weddell Sea, Ross Sea, Prydz Bay, and Adélie Coast– over the period 1980–2024. We compute the net ocean heat budget (OHB) as the combined effect of radiative, turbulent, and conductive fluxes, focusing on the austral autumn and winter months (March–October), when ocean–atmosphere exchange is most active in promoting dense water formation. The analysis reveals a consistent reduction in oceanic heat loss across all regions, particularly pronounced after the mid-2010s, with the largest decline observed in the Weddell Sea (32%). These reductions are primarily linked to declining sensible heat fluxes associated with notable increases in 2-m air temperature (up to 0.2 °C per decade), thereby weakening thermal gradients and turbulent heat exchanges. Sea surface temperature and sea-ice concentration showed minimal interannual variability, underscoring atmospheric forcing as the primary driver of observed trends.